BiOCl/cattail carbon composites with hierarchical structure for enhanced photocatalytic activity. (15th November 2020) - Hou, Jianhua; Dou, Qian; Jiang, Ting; Yin, Jin; Liu, Junli; Li, Yuanyuan; Zhang, Geshan; Wang, Xiaozhi
Highlights: Cattail carbon is derived from direct carbonized withered cattail. BiOCl with hierarchical structure grows on the surface of cattail carbon. Cattail carbon can act as an electron acceptor to transfer photoelectrons. Treatment of acetic acid makes BiOCl have ultrathin nanosheets. One-step coprecipitation route with stirring is used for composites synthesis. Abstract: Bismuth oxychloride (BiOCl) has great potential as a photocatalytic material. It is worthy to improve its photocatalytic performance by a simple and feasible method. In this work, withered cattail is carbonized directly at 800 ℃ in nitrogen atmosphere to obtain cattail carbon with good conductivity, which could be a good acceptor of photogenerated electrons. Through the one-step facile co-precipitation route with stirring at room temperature followed by the treatment of acetic acid, ultrathin nanosheets of BiOCl were synthesized and grew on the surface of cattail carbon. The BiOCl/cattail carbon composites have well-contacted heterojunction interface, hierarchical structure, high specific surface area and enhanced utilization of visible light, which allow the composites to separate the photogenerated electron-holes efficiently. Thus the BiOCl/cattail carbon composites could show excellent photocatalytic activity, which could remove rhodamine B completely within one hour under visible light. The degradation rate of the composite could achieve about 17 times higher than that of pure BiOCl. Mechanism test showed that both OH and h + active species could work together to degrade organic pollutants. Therefore, our work combines readily available and inexpensive biochar materials with BiOCl, which provides a strategy for the low-cost synthesis of efficient BiOCl-based photocatalytic materials that can be used in large-scale industrial production to be applied in the treatment of organic wastewater.